(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Gli interventi del presidente Macron del 2018 e la battaglia contro il “separatismo islamista” - 2. Il percorso del progetto di legge “confortant le respect des principes de la République” - 3. Struttura e principali contenuti della legge - 3.1. “Garantir le respect des principes de la République et des exigences minimales de la vie en société” - 3.2. “Garantir le libre exercice du culte” - 4. “Qualcosa di nuovo, anzi di antico”. The French law 24th August 2021, no. 1109, “consolidating respect for the principles of the Republic” ABSTRACT: In October 2020, President Emmanuel Macron announced his intention to sponsor a law opposing “Islamic separatism” in French society. Introduced in December 2020 by the Interior Minister Gérald Darmanin, the bill contains measures on neutrality of the public service, fight against online hatred, protection of civil servants (e.g. teachers) and several criminal provisions, which aim at repressing conducts denoting radicalism. The French Parliament passed the controversial law - it is sometimes described as going contrary to the liberal values of the Republic that it seeks to protect - on 23rd July 2021 and President Macron promulgated it on 24th August. The contribution provides an overview of the new law.